Re-accessing: Recreating the corner tower as public building through methods of re-enactment - Revuelta Petersson, Malin (My University, 2025)
The thesis explores the corner tower as a prom inent but inaccessible part of the urban fabric. The elaborate ornamentality that this typology represents resembles the monument. But unlike the monument the corner tower is private, ac cessible to the public only as a distant ornament. The private nature of the corner tower reduces it to an anonymous object. Built as a symbol of status it is now a historical remnant without obvi ous purpose, its visual identity unquestioned and spatial experience unexplored. The project brings the corner tower to ground level, altered into an installation focusing both on visual identity and spatial experience. The theory of re-enactment as explanation for architectural development is applied in a series of methods to document and gradually alter the visual identity of the corner tower. Through a new architectural work, the symbolic meaning as well as the possi bilities of the corner tower is presented. The aim of the thesis is to explore the methods related to architectural re-enactment by rein terpreting the visual and spatial experience of the corner towers in a new work. The question explored in the thesis is; How can values and meanings be transferred from an original to a new work of architecture through methods of re-enactment? A collection of corner towers in central Gothen burg is through the methods of quotation, para phrase and spoliation documented, altered and repurposed in a new design project. Their spatial possibilities are elaborated and their decorative elements are reinterpreted through experimental design. The design project consists of different installa tions, connected to the visual and symbolic val ues of the corner towers. The corner tower has through the methods of re-enactment been rein terpreted into a fortress, a series of follies and a watchtower. All three typologies are contesting the inaccessible nature of the corner towers. Translated to a new context, the designs rep resent a fragment of the architecture history of Gothenburg. The locus is on the spatial possibili ties of the corner tower as well as its ornamental nature. The result is a re-enactment of the cor ner tower, radically changed but still connected to the same visual identity that inspired it.